Amphibian-derived wound healing peptides: chemical molecular treasure trove for skin wound treatment - Yin, Saige; Wang, Ying; Yang, Xinwang (Frontiers in Pharmacology, 2023)
Amphibian-derived wound healing peptides thus offer new intervention measures and strategies for skin wound tissue regeneration. As novel drug lead molecules, wound healing peptides can help analyze new mechanisms and discover new drug targets. Previous studies have identified various novel wound healing peptides and analyzed novel mechanisms in wound healing, especially competing endogenous RNAs (ceRNAs) (e.g., inhibition of miR-663a promotes skin repair). In this paper, we review amphibian-derived wound healing peptides, including the acquisition, identification, and activity of peptides, a combination of peptides with other materials, and the analysis of underlying mechanisms, to better understand the characteristics of wound healing peptides and to provide a molecular template for the development of new wound repair drugs.